The role of a urine dipstick in the diagnosis of the acute scrotum - Sophie Tissot; Christopher Perrott; Richard Grills (BJUI Compass, 2022)
Abstract Objective To evaluate the role of a urine dipstick in the assessment of acute scrotal pain emergency department presentations. Methods A single institution, prospective case series, from February 2020 to February 2021. All patients who received a bedside review by a urology doctor for acute scrotal pain were included. Urine dipstick results were pre‐defined as having had an impact on the emergency clinician's diagnosis if it showed pyuria and/or nitrituria and the final diagnosis was epididymitis‐orchitis or haematuria and the final diagnosis was ureterolithiasis. Results 139 patients presented to the emergency department with a complaint of acute scrotal pain. 85 (61%) were referred for bedside urology review. Median age of 17 years (P25 12 yrs, P75 31 yrs). 2.3% (n = 2) had proven testicular torsion, 28.5% (n = 24) had epididymitis‐orchitis and 8.2% (n = 7) had ureterolithiasis. 68 (80%) of patients received a primary diagnosis of testicular torsion by the emergency department clinician. Following review by a urology unit doctor, 14 proceeded to scrotal exploration for concern of testicular torsion. 7 patients were diagnosed with ureterolithiasis, all of whom had haematuria on their urine dipsticks (100%, 95% CI: 59–100%), 100% of these urine dipsticks were initiated by the urology unit doctor following bedside review. 22 patients were diagnosed with epididymitis‐orchitis. 8 of these had pyuria, nitrituria and/or haematuria on their urine dipstick (36%, 95% CI: 17–59%) and only one urine dipstick was completed prior to referral. 20.6% of patients perceived to have testicular torsion by the emergency department had a positive urine dipstick that aligned with their final alternative diagnosis (95% CI: 12–32%). Conclusion A collection of clinical findings is required to diagnose the aetiology of acute scrotal pain. Information that can be easily, quickly, cheaply, and reliably collected, such as a urine dipstick, can assist in clinical decision making.